Cryosphere hazards in Ladakh: the 2014 Gya glacial lake outburst flood and its implications for risk assessment - Schmidt, Susanne; Nüsser, Marcus; Baghel, Ravi; Dame, Juliane (Natural hazards, 2020)
This article attempts to reconstruct the causes and consequences of the 2014 glacial lake outburst flood (GLOF) event in Gya, Ladakh. We analyse the evolution of the Gya glacial lake using a high temporal and high spatial resolution remote sensing approach. In order to frame the case study in a larger picture, we produce a comprehensive inventory of glacial lakes for the entire Trans-Himalayan region of Ladakh. Changes in the extent and number of glacial lakes have been detected for the years 1969, 1993, 2000/02 and 2018 in order to assess the potential risk of future GLOFs in the region. The remote sensing approach was supported by field surveys between 2014 and 2019. The case study of the Gya GLOF illustrates the problem of potentially hazardous lakes being overlooked in inventories. The broader analysis of the Ladakh region and in-depth analysis of one GLOF lead us to propose an integrated approach for detecting undocumented GLOFs. This article demonstrates the necessity for using multiple methods to ensure robustness of risk assessment. The improved understanding can lead to a more accurate evaluation of exposure to cryosphere hazards and identification of alternative mechanisms and spatial patterns of GLOFs in the Himalaya.